Thirty-eight-year follow-up of two sibling Lipoid Congenital Adrenal Hyperplasia patients due to homozygous Steroidogenic Acute Regulatory (STARD1) protein Mutation. Molecular structure and modeling of the STARD1 L275P mutation. - Lehoux, Jean-Guy (Frontiers in Neuroscience, 2016)
Objective: Review the impact of StAR (STARD1) mutations on steroidogenesis and fertility in LCAH patients. Examine the endocrine mechanisms underlying the pathology of the disorder and the appropriate therapy for promoting fertility and pregnancies. Design: Published data in the literature and a detailed 38-year follow-up of two sibling LCAH patients. Molecular structure and modeling of the STARD1 L275P mutation. Setting : University hospital. Patients: Patient A (46,XY female phenotype) and patient B (46,XX female) with LCAH bearing the L275P mutation in STARD1. Interventions : Since early-age diagnosis, both patients underwent corticoid replacement therapy. Patient A received estrogen therapy at pubertal age. Clomiphene therapy was given to Patient B to induce ovulation. Pregnancies were protected with progesterone administration. Main Outcome Measures : Clinical and molecular assessment of adrenal and gonadal functions. Results: Both patients have classic manifestations of corticosteroid deficiency observed in LCAH. Time of onset and severity were different. Patient A developed into a female phenotype due to early and severe damage of Leydig cells. Patient B started a progressive pubertal development, menarche and regular non-ovulatory cycle. She was able to have successful pregnancies. Conclusions: Understanding the molecular structure and function of STARD1 in all steroidogenic tissues is the key for comprehending the heterogeneous clinical manifestations of LCAH, and the development of an appropriate strategy for the induction of ovulation and protecting pregnancies in this disease.